Unilateral Renal Agenesis in Kitten - Ferreira, Hellen Mariana; Assis, Maisa Martins Quirilos; Marangon, Willian Fontini; da Silva, Mariane Cynara; de Melo, Jaqueline Bruna; de Carvalho, Raquel Jordana de Mello Pires; Gusso, Ana Bianca Ferreira; Merlini, Natalie Bertelis (Acta Scientiae Veterinariae, 2022)
Background: The kidneys are a pair of organs that maintain homeostasis, and perform hormonal and excretory functions; the functional unit of the kidney is the nephron. Approximately 2% of cats are born with some structural or functional anomaly, which occurs during fetal development. Unilateral renal agenesis is a rare congenital anomaly in felines, where the cat has only one kidney. This can lead to a series of dysfunctions, with clinical signs, especially when the contralateral organ does not adequately compensate, since there is more than one concomitant congenital disease like kidney dysplasia, which is the abnormal formation of the kidney structures. This study aimed to report the case of a kitten diagnosed with unilateral renal agenesis; the clinical signs, diagnosis, and treatment. Case: A 2-month-old mixed breed female kitten, weighing 0.5 kg, was attended in a veterinary clinic with emesis, hyporexia, hypodipsia, normuria, and diarrhea. Upon physical examination, dehydration, hyperthermia, and renomegaly by abdominal palpation were observed. Complementary examinations such as serum urea and creatinine estimation, abdominal ultrasound, and excretory urography, were requested, and the results include hemoglobin (9 g/dL), mean corpuscular volume (26%), normocytic normochromic anemia, urea (312 mg/dL), and creatinine (3.5 mg/dL). The abdominal ultrasound showed renomegaly on the left kidney and the absence of the right kidney. The above results and excretory urography help to confirm the diagnosis of unilateral renal agenesis and suggested renal dysplasia. The patient was hospitalized to stabilize her condition. The treatment is symptomatic and supportive and aims to increase the patient’s quality of life. Treatment with metoclopramide, erythropoietin, fluid therapy with ringer’s lactate solution, and renal therapeutic feed was prescribed. After 4 days of hospitalization and treatment, the serum creatinine was within normal parameters for the species and the animal showed no more clinical signs. She was discharged and was treatment continued at home. After 36 days, the patient returned for reevaluation: the tutor reported that the patient did not present with episodes of emesis, was active, with normodipsa and normuria, and via abdominal palpation, there was no renomegaly of the left kidney; serum creatinine and urea levels were below and within the reference values, respectively. Discussion: Unilateral renal agenesis is a rare congenital anomaly in small animals and is characterized by the absence of one of the kidneys; in felines, its etiopathogenesis remains unclear. When the clinical signs are present, these are similar to those of chronic kidney disease. The most frequent signs are weight loss, polyuria and polydipsia, hyporexia or anorexia, emesis, halitosis, gastroenteritis, and gastric ulcers; some of them were presented by the patient in this study. Serum urea and creatinine levels are important to evaluate if there are alterations in the remaining kidney, which was detected in the initial examination. The diagnosis is made through imaging tests such as ultrasonography and excretory urography, used in this case for diagnosis. The treatment is symptomatic and supportive and aims to increase the quality of life of the patient. An antiemetic should be prescribed for patients with emesis, and the most used are maropitant, metoclopramide, and ondansetron. The diet must be changed; to reduce azotemia, therapeutic meals that aid renal functions are recommended. Unilateral renal agenesis is a rare anomaly in small animals, which can cause damage to the animal. Understanding this damage is essential in determining of the conduct by the veterinarian. Keywords: kidneys, azotemia, congenital, anomaly, feline. Título:Agenesia renal unilateral em gatinha Descritores: rins, azotemia, congênita, anomalia, felino.